Adopsi Cloud Enterprise Resource Planning dengan Pendekatan Technology, Organization, and Environmental pada UMKM: Tinjauan Literatur - Hasan, Annisa Nabilah; Liwan, Nadhilah Amaliah; Sudharma, Falih Zaki; T. Pontoh, Grace; Indrijawati, Aini (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2025)
Purpose: This research aims to encourage MSMEs to adopt Cloud Enterprise Resource Planning (ERP) to deal with resource limitations, with Technology, Organization, and Environmental (TOE) approach based on previous research.Method: The research method uses systematic literature review analysis with the help of Watase Uake, Publish or Perish, Science Direct, IEEE, Scopus, Taylor and Francis, Google Scholar, ProQuest by producing 33 scopus articles that match the research topic.Results: The results show that the most influential factor in adopting cloud ERP is the technological factor because it is the core of using cloud ERP technology. The second and third factors are influenced by organizational factors and environmental factors. Apart from cloud ERP adoption factors, there are challenges that MSMEs need to face, especially related to costs because they involve initial investment and operational costs.Implications: This research implies the government to support the adoption of cloud ERP by MSMEs through policies such as fiscal incentives, subsidies, and training. For MSMEs and society, this research shows the benefits of cloud ERP in improving efficiency, competitiveness, and product innovation.Novelty: This research may offer new insights into effective strategies or solutions to overcome the identified challenges.